Determination of Cell Permeabilization and Beta-Galactosidase Extraction from Aspergillus oryzae CCT 0977 Grown in Cheese Whey - Caroline dos Santos Viana; Denise Renata Pedrinho; Luiz Rodrigo Ito Morioka; Hélio Hiroshi Suguimoto (International Journal of Chemical Engineering)
Aspergillus oryzae grown in cheese whey has the ability to produce beta-galactosidase. The objective of this work was to define the parameters for the determination of cell permeabilization and extraction of the enzyme from Aspergillus oryzae CCT 0977 biomass, with high enzymatic activity. The Box–Behnken design was used to determine cell permeabilization and extraction of beta-galactosidase conditions. The fermentation was carried out for a period of 5 days at 28°C, having as substrate the deproteinized cheese whey. To determine the effect of the variables on beta-galactosidase activity, enzymatic activity was determined by the lactose hydrolysis reaction. The most efficient condition for cell permeabilization was 25% ethanol at 30°C for 90 min, obtaining an enzymatic activity of 0.44 U·mL−1. For beta-galactosidase extraction from the biomass, the most efficient condition was 5.3% chloroform at 48°C, with an enzymatic activity of 0.17 U·mL−1. The use of ethanol was most efficient to promote cell permeability of Aspergillus oryzae CCT 0977.